Preharvest Ethephon spray on fruit quality and increasing the rate of ripening of date palm fruit (Phoenix dactylifera L.) cv. Helali - Al-Saif, Adel Mohammed; Alebidi, Abdullah Issa; Al-Obeed, Rashid Sultan; Soliman, Said Saad (Progress in Nutrition, 2017)
This study was conducted at the Dirab, to study the effect of fruits date (bisir stage) spray by ethephon solution on fruit physical and chemical properties. Results showed that spraying ethephon significantly affected by different treatments for Helali cultivar in both seasons of study. It was clearly noticed that there is a positive relationship between ethephon concentrations and fruit physical and chemical properties. Meanwhile, found there is a direct correlation between the concentrations of ethephon and increase the proportion of rutab date. Ethephon treated fruits at 1500 ppm resulted in decreased fruit dimension, flesh weight, fruit weight, fruit volume, total acidity percentage and moisture content. In addition, increased of total soluble solids, reducing and total sugars percentage at rutab stage during in both seasons of study compared to the control at harvest. It is concluded that spray by ethephon on bisir stage of Helali date fruit for increasing the proportion of ripening and rutab date moreover early harvest.